Population parameters and exploitation level of striped snakehead, Channa striata (Bloch, 1793) in Aopa Swamp, Southeast Sulawesi - Bahrin, Nurtini; La Sara, La Sara; Asriyana, Asriyana (AQUASAINS, 2020)
Striped snakehead is one of the important economical fish in Aopa Swamp waters. Research on population parameters and exploitation level of striped snakehead was conducted from November 2018 to January 2019. The objective of this research was to analyze population parameters and exploitation level of striped snakehead in the Rawa Aopa waters in Southeast Sulawesi. Fish samples were caught using a fishing trap used by fishermen. A total of 449 individual fish were caught with ranging 20.0-47.0 cm in length and 59.0-994.0 g in weight. Striped snakehead has an isometric growth pattern (b=3.08 ; r=0.96, R2=0.92) with the equation model W=6.10-3L3,08. Striped snakehead reaches its maximum length in size L ͚ = 48.62 cm with a growth coefficient (K) of 0.68 year-1. Fishing mortality (F= 0.87) is higher than natural mortality (0.63). Exploitation level of striped snakehead in Rawa Aopa waters is categorized as overfishing (E> 0.5).Keywords : Striped snakehead, isometrics, overfishing, Aopa Swamp, Southeast Sulawesi